Silver bullets: a new lustre on an old antimicrobial agent - Möhler, Jasper; Sim, Wilson; Blaskovich, Mark A. T.; Cooper, Matthew A.; Ziora, Zyta M. (Biotechnology advances, 2018)
Silver was widely used in medicine to treat bacterial infections in the 19th and early 20th century, up until the discovery and development of the first modern antibiotics in the 1940s, which were markedly more effective. Since then, every new antibiotic introduced to the clinic has led to an associated development of drug resistance. Today, the threat of extensive bacterial resistance to antibiotics has reignited interest in alternative strategies to treat infectious diseases, with silver regaining well-deserved renewed attention. Silver ions are highly disruptive to bacterial integrity and biochemical function, with comparatively minimal toxicity to mammalian cells. This review focuses on the antimicrobial properties of silver and their use in synergistic combination therapy with traditional antibiotic drugs.
Gesehen am 06.05.2020